Work-Falimy Balance dan Job Satisfaction pada Working Mom sebagai Perawat - Kakiay, Thalia Eleison Esther (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Job satisfaction is defined in terms of pleasure and reward. It includes an evaluative assessment of one's job or work situation, reflecting their response to the characteristics, challenges, and benefits of their job. Work-Family Balance is a comprehensive evaluation of the achievement of roles carried out by individuals in connection with the expectation of negotiation and division of roles with partners in carrying out their roles both in the realm of work and family. This study is to determine whether there is a correlation between Work-Family Balance and Job satisfaction in working moms as nurses. using a quantitative approach with a total of 88 participants obtained using purposive sampling technique. The data collection tool is the Job Satisfaction scale by Hills et al, (2011) of 10 items and the Work-family Balance scale by Carlson et al, (2009) of 6 items. Data analysis used non-parametric correlation test techniques. The correlation test results show a Spearman's rho value of r = 0.452 with a significance value of p = 0.000 (p < 0.05), which means that there is a fairly strong positive relationship between Work-Family Balance and Job Satisfaction in working moms as nurses. Thus, the better the Work-Family Balance that nurses have, the Job Satisfaction also tends to increase.